Parenting practices, self-control and anti-social behaviors: Meta-analytic structural equation modeling - Tehrani, Hossein Dabiriyan; Yamini, Sara (Journal of criminal justice, 2020)
This study aims to clarify the nexus between effective parenting practices, low self-control, and anti-social behaviors in Gottfredson and Hirschi's General Theory of Crime (GTC). The analysis included 72 articles reporting 255 effect sizes (N = 94,604). We used the method of Meta-Analytic Structural Equation Modeling (MASEM) to test the assumptions of GTC. The results of the MASEM revealed that low self-control is a positive and in magnitude modest determinant of anti-social behaviors (β = 0.27, p < .05). The effective parenting practice is negative, of small size, and also a statistically significant determinant of low self-control (β = −0.2). We observed that effective parenting practice is statistically significant and, in magnitude, shows small size negative direct and indirect effects on anti-social behaviors (β = −0.126 and β = −0.053, respectively). Low self-control partially mediated the relationship between effective parenting practices and anti-social behaviors. Consistent with the construct of aggregated effective parenting practices, we found uniform patterns for models performed across elements of effective parenting practices with low self-control and anti-social behaviors. The results of moderator analyses showed that the association between low self-control and anti-social behaviors tended to be stronger when the individualistic score of countries improved. •The current meta-analysis is the first effort using the MASEM methods to test the assumptions of GTC and bridge the gap in the literature. This study, based on MASEM, showed that partial mediation is a model that presents the data better than the full mediation model.•The results of MASEM added to the literature by showing that there are similar trends between the construct of aggregated effective parenting practices and their elements (i.e., emotionally supportive practices, monitoring, recognition, and effective discipline) with low self-control and anti-social behaviors.•We used TSSEM viewed as the state-of-the-art method to perform MASEM. Inconsistencies were explained by categorical moderator analyses through TSSEM and OSMASEM, and also continuous moderator analyses through OSMASEM.•We employed parameter-based MASEM (using bootstrap and delta methods) and Full Information Meta-Analytic Structural Equation Modeling (FIMASEM) to show the generalizability and heterogeneity of Structural Equation Modeling (SEM) parameters.•We applied studentized deleted residuals to assess outlier analysis and conducted different methods (i.e., TSSEM with corrected correlation, Univariate-r MASEM, FIMASEM, OSMASEM) to perform MASEM to check the robustness of the findings. We also used multiple methods of assessing for publication bias, namely, funnel plot, trim and fill analysis, Fail-safe N, and Egger's test.